Books Go Public: The Consequences of the Expropriation of Monastic Libraries on Innovation - Paolo Buonanno; Francesco Cinnirella; Elona Harka; Marcello Puca (Center for Economic Studies and ifo Institute (CESifo), 2024)
Access to useful knowledge is crucial for fostering modern economic growth. We show, for the first time, that knowledge accumulated and stored in monasteries was useful for innovation. In 1866, anticlerical legislation in Italy led to the suppression of religious orders, the expropriation of their properties, and the transfer of their manuscripts to local public libraries. From a contemporary survey on public libraries, we construct a unique dataset on municipalities which received monastic volumes. This information is then linked to newly digitized annual data on patents issued in Italy between 1863 and 1883. Difference-in-differences estimates show that municipalities exposed to an influx of monastic manuscripts experienced a significant increase in innovation. The effect is driven by the increase in the number of manuscripts in previously existing libraries. We show that the innovation advantage also persisted in the long run and had no impact on human capital.
Keywords: N33; O30; Z12; 330; books; manuscripts; knowledge; religion; monastery; libraries; patents